In situ imaging of the dynamics of photo-induced structural phase transition at high pressures by picosecond acoustic interferometry. (26th May 2017) - Kuriakose, Maju; Chigarev, Nikolay; Raetz, Samuel; Bulou, Alain; Tournat, Vincent; Zerr, Andreas; Gusev, Vitalyi E
Abstract: Picosecond acoustic interferometry is used to monitor in time the motion of the phase transition boundary between two water ice phases, VII and VI, coexisting at a pressure of 2.15 GPa when compressed in a diamond anvil cell at room temperature. By analyzing the time-domain Brillouin scattering signals accumulated for a single incidence direction of probe laser pulses, it is possible to access ratios of sound velocity values and of the refractive indices of the involved phases, and to distinguish between the structural phase transition and a recrystallization process. Two-dimensional spatial imaging of the phase transition dynamics indicates that it is initiated by the pump and probe laser pulses, preferentially at the diamond/ice interface. This method should find applications in three-dimensional monitoring with nanometer spatial resolution of the temporal dynamics of low-contrast material inhomogeneities caused by phase transitions or chemical reactions in optically transparent media.